A midsummer night's dream - Shakespeare, William, 1564-1616 (Shakespeare, William, 1564-1616. Works. 2003., 2005)
From the hilarious mischief of the elf Puck to the rough humor of the self-centered Bottom and his fellow players, from the palace of Theseus in Athens to the magic wood where fairies play, Shakespeare's marvelous A Midsummer Night's Dream is a play of enchantment and an insightful portrait of the predicaments of love.